Pengaruh Teknik Relaksasi Genggam Lima Jari dengan Murottal Al-Qur’an Terhadap Intensitas Nyeri Insisi Pada Pasien Post Sectio Caesarea: Case Report - Destiana, Adelia Viranissa; Puspita, Dewi; Retno Wulandari, Catharina Wahyu (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Abstract. Caesarean section (SC) is a surgical delivery process where the baby is removed through an incision in the mother's stomach and uterus. Post-SC patients will experience the impact of pain, because it is caused by surgery. The nursing intervention of the five-finger handheld relaxation technique with murottal Al-Qur'an is one effort to reduce pain in post-caesarean section patients. The research method uses case reports (case repost). The research sample was 3 mothers post SC on the first day. The measurement instrument uses a numerical scale to measure the pain scale in patients. The intervention of the five-finger handheld relaxation technique with murottal Al-Qur'an was carried out for 2 days when the patient was hospitalized 1x/day and observations were made to determine the pain scale before and after the intervention. The results of the intervention showed that the pain in the three respondents before the five-finger grasp relaxation technique with Al-Qur'an murottal was carried out experienced a severe pain scale and after the intervention was carried out it decreased, namely the severe pain scale became moderate.